2019
DOI: 10.3390/ijms20194690
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Carcinogenesis Mechanism: DNA Damage

Abstract: Nickel (Ni) is known to be a major carcinogenic heavy metal. Occupational and environmental exposure to Ni has been implicated in human lung and nasal cancers. Currently, the molecular mechanisms of Ni carcinogenicity remain unclear, but studies have shown that Ni-caused DNA damage is an important carcinogenic mechanism. Therefore, we conducted a literature search of DNA damage associated with Ni exposure and summarized known Ni-caused DNA damage effects. In vitro and vivo studies demonstrated that Ni can indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(42 citation statements)
references
References 181 publications
(220 reference statements)
0
42
0
Order By: Relevance
“…In the current study, in order to investigate the cytotoxicity and immune response caused by exposure to low concentrations of the heavy metals, Ni and Cd, which are known to have cytotoxicity and cause immune toxicity [ 8 , 9 ], were selected. Ni generally enters cells through transferrin or divalent metal transporter-1 (DMT1) and exhibits cytotoxicity by inhibiting DNA repair processes or causing oxidative stress through the depletion of intracellular antioxidants such as glutathione [ 16 , 17 ]. Cd enters cells through the ZIP (ZRT, IRT-like protein) transporter, metallothionein, and DMT1 (divalent metal transporter-1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, in order to investigate the cytotoxicity and immune response caused by exposure to low concentrations of the heavy metals, Ni and Cd, which are known to have cytotoxicity and cause immune toxicity [ 8 , 9 ], were selected. Ni generally enters cells through transferrin or divalent metal transporter-1 (DMT1) and exhibits cytotoxicity by inhibiting DNA repair processes or causing oxidative stress through the depletion of intracellular antioxidants such as glutathione [ 16 , 17 ]. Cd enters cells through the ZIP (ZRT, IRT-like protein) transporter, metallothionein, and DMT1 (divalent metal transporter-1).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that 50 nM of Ni and 10 nM of Cd alone did not have a significant effect on cell viability; however, when the two heavy metals were used in mixture at these concentrations, cell viability was significantly lower than that of the control group after 48 h. Studies on the synergic [ 23 , 24 ] and antagonistic [ 25 , 26 ] effects of heavy metal co-exposure have been conducted, and their results suggest that the mixed exposure of Ni and Cd has a synergic effect on cell viability. Differences in cell entry and cytotoxic mechanisms of Ni and Cd [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ] have been identified; therefore, their individual properties may be related to these synergic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) identified nickel compounds as Class I carcinogenic materials 1,2 . But the toxicity of nickel oxide (NiO) did not attract much attention until the rise of nanotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…There appears to be less within-group variation in BEAS-2B group. All these heavy metals and metalloid are directly or indirectly associated with the development of lung cancer [ [94] , [95] , [96] , [97] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%